APPLICATION OF COOPERATIVE LEARNING TYPE THINK PAIR SHARE COMBINED MAKE A MATCH TO PRACTICE COMMUNICATION SKILLS ON ACID BASE MATERIALS - Indah Nur Safitri; Harun Nasrudin (JCER (Journal of Chemistry Education Research), 2022)
The goals of this research to describe the application of cooperative learning model of Think Pair Share combined Make a Match, student activities, communication skills, learning outcomes, and student responses. The research design used was One Group Pretest-Posttest design with a sample of 36 students in class XI IPA 4 MAN Sidoarjo. The results showed that (1)Implementation model at three meetings in a row obtained a percentage of 89.58%; 89.58% and 95.83%. (2)Student activities at three meetings successively got a percentage of 97.96%; 95.56%; 96.11%. (3)Communication skills in the form of the quantity questions in three meetings with a percentage of 27.78%; 36.11% and 41.67% with quite good category, and the number of students' opinion in three meetings with a percentage of 36.11%; 55.56% and 72, 22%. Communication skills in the form of quality questions and opinions of students in three meetings with the number of students a good predicate of 3 and 12 students; 7 and 15 students; 6 and 19 students. (4)Student learning outcomes obtain an average score of 80.67, while classical completeness student learning outcomes of 88.89%. (5)Positive responses of students obtain an average percentage of 92.01% with very good criteria.